Mean Level of Protein C, Protein S and Antithrombin lll in Pediatric Nephrotic - Imtiaz, Rumana; Naveed , Muhammad Asif; Fatima , Javaria; Irum, Saima; Yaseen, Shazia; Rafi, Sarah (Pakistan BioMedical Journal, 2022)
The triad of clinical symptoms linked with proteinuria of nephrotic range, including hypoalbuminemia and edema, is known as nephrotic syndrome. When body excrete more than40 mg/m2/hr of protein or a first morning protein: creatinine ratio of more than 2-3: 1 then we call it proteinuria of nephrotic range.(1)It is estimated that the vast majority of children with nephrotic syndrome have some form of primary or idiopathic sickness, with minimal change disease being the most prevalent.Thromboembolic consequences are more common in people who have nephrotic syndrome. (2) This study tends to shed light if there is increase or decrease in level of protein C, S or antithrombin III in nephrotic syndrome. OBJECTIVE: To determine the mean level of protein C, protein S and AT Ill in children with nephrotic syndrome. SETTING: The research was conducted at Department of Haematology at Children Hospital Lahore. STUDY DESIGN: Cross sectional study. DURATION OF STUDY: The study was completed in six months from 25-08-2017 to 29-02-2018. DATA COLLECTION PROCEDURE: Patients fulfilling the inclusion criteria were taken for Protein C, Protein S and Antithrombin III assays Collect blood 3ml (9 vol) in 0.109M (3.2%) anticoagulant (1 Vol) and Centrifuge. All centrifuge specimens were run in DIAGNOSTIC STAGO. Results: A total of 100 children with nephrotic syndrome were enrolled after fulfilling inclusion criteria. The mean age of the children was 6.26±2.72 month. 69(69%) were male children. Protein C level was 95.31±16.02, Protein S level 84.05±13.31 and antithrombin III level was 86.50±16.36. Conclusion: Protein C, S and Antithrombin III level were within normal range. Further studies are needed to delineate the exact pathogenesis behind thromboembolic phenomenon in nephrotic syndrome children.